Pengaruh Gaya Kognitif Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Halida Eka Nurmutia (Edumatika : Jurnal Riset Pendidikan Matematika, 2019)
The objective of this study is to determine the effect of cognitive style on students’ mathematical problem-solving ability. This study used the survey method with a quantitative approach. One class consisting of 32 students was selected by purposive sampling for the study sample. A total of 17 students have a field-dependent (FD) cognitive style, while 15 other students have a field independent (FI) cognitive style. GEFT and mathematical problem-solving ability test instruments were used to collect research data. Data were analyzed using Pearson Product Moment correlation test and a simple regression test. The research results found that there is a strong positive relationship between cognitive style and students’ mathematical problem-solving ability, indicated by correlation coefficient r = 0,636. In addition, cognitive style has an effect on students’ mathematical problem solving ability of 40,5% through a linear relationship Ŷ = 3,703 + 0,512X.